Competence And Performance Of Teachers In Certified Teachers Social Studies Learning In Middle Schools - Zulkarnain Zulkarnain; Nani Suwarni; Sudarmi Sudarmi; Irma Lusi Nugraheni (Journal Learning Geography, 2021)
The purpose of this study was to analyze the performance of the competencies and performance of certified teacher educators in social studies in junior high schools in Way Kanan District: the problems and their solutions. The method used in this research is descriptive qualitative method. The subjects of the study were 48 Social Sciences certified SMP teachers and 5 principals as respondents. Data collection tools used were questionnaire and documentation techniques. Data analysis techniques using percentages. Research results that; 1) Social studies teachers' pedagogical and professional competencies are good, 2) The performance of social studies teachers who have passed certification as a whole has been classified as good when viewed from indicators of the ability of teachers to implement and evaluate learning. However, the teacher's ability to plan learning still needs to be improved. 3) Difficulty in getting teaching aids is a major problem faced by social studies teachers who have passed certification in Geography learning. Also, difficulties in understanding physical geography material, 3) Efforts to overcome the problem by means of connectivity on the internet and ask fellow social science teachers in MGMP forums. Keywords: competence, performance, junior high school social science teacherTujuan dari penelitian ini adalah untuk menganalisis kinerja kompetensi dan kinerja pendidik guru bersertifikat dalam studi sosial di sekolah menengah pertama di Kabupaten Way Kanan: masalah dan solusinya. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Subjek penelitian adalah 48 guru IPS bersertifikasi IPS dan 5 kepala sekolah sebagai responden. Alat pengumpulan data yang digunakan adalah teknik kuesioner dan dokumentasi. Teknik analisis data menggunakan persentase. Hasil penelitian itu; 1) Kompetensi pedagogik dan profesional guru mata pelajaran IPS baik, 2) Kinerja guru mata pelajaran sosial yang telah lulus sertifikasi secara keseluruhan telah diklasifikasikan baik jika dilihat dari indikator kemampuan guru untuk menerapkan dan mengevaluasi pembelajaran. Namun, kemampuan guru untuk merencanakan pembelajaran masih perlu ditingkatkan. 3) Kesulitan dalam mendapatkan alat peraga adalah masalah utama yang dihadapi oleh guru IPS yang telah lulus sertifikasi dalam pembelajaran Geografi. Juga, kesulitan dalam memahami materi geografi fisik, 3) Upaya untuk mengatasi masalah melalui konektivitas di internet dan bertanya kepada sesama guru ilmu sosial di forum MGMP. Kata kunci: kompetensi, kinerja, guru sains sosial SMP